Association of single nucleotide polymorphism in patatin like phopholipase domain containing 3 (PNPLA3) gene with paediatric non-alcoholic fatty liver disease - Alam, Rubaiyat; Fathema, Kaniz; Rukunuzzaman, Md; Nahid, Khan Lamia; Mahbuba, Sharmin; Akram, Lubana; Sattar, Abu Naser Ibne (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Background: Non-alcoholic fatty liver disease (NAFLD) is the most unabating cause of chronic liver disease in children and adolescents. This study aimed to examine the association of single nucleotide polymorphism in patatin-like phospholipase domain containing 3 (PNPLA3) gene with paediatric non-alcoholic fatty liver disease. Methods: This case-control study was conducted from June 2021 to December 2022. Fifty-one overweight children aged 6–17 years were recruited in this study and divided into NAFLD (cases) and non-NAFLD (controls) groups based on hepatic steatosis detected by liver ultrasonography. We analysed the rs738409 polymorphism by TaqMan assay and examined its association with NAFLD. Results: Thirty-one (60.8%) children were in the case group and 20 (39.2%) children were in the control group. Alanine aminotransferase (P<0.001) and triglycerides (P=0.02) were found to be significantly higher in cases. However, no significant association was found between the PNPLA3 rs738409 single nucleotide polymorphism (SNP) and the presence of NAFLD in children. Conclusion: Our study didn't find any association between PNPLA3 rs 738409 single nucleotide polymorphisms and presence of NAFLD in children, but we discovered that high alanine aminotransferase and triglycerides level can be useful in screening overweight children for NAFLD. Bangabandhu Sheikh Mujib Medical University Journal 2023;16(3): 139-143